2010
DOI: 10.1590/s0104-56872010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Controle postural de escolares com respiração oral em relação ao gênero

Abstract: TEMA: controle postural de escolares com respiração oral. OBJETIVO: comparar postura e equilíbrio corporal entre os grupos de escolares com e sem respiração oral considerando a variável gênero. MÉTODO: o estudo foi realizado em uma escola municipal da cidade de Santa Maria; foi aprovado pelo Comitê de Ética da Universidade Federal de Santa Maria. O grupo estudo (com respiração oral) e o grupo controle (sem respiração oral) foram selecionados, baseados na anamnese, na idade (entre 8 a 12 anos), na avaliação do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Studies have shown that swallowing is an activity which is coordinated with other oral functions and require a strict interaction among different muscle groups. For the synchronization of suction and swallowing, it is necessary a strict relationship between the muscles of the oral region to generate suction pressure, to open and close the mouth, and of the tongue to make the bolus and its peristaltic transportation into the pharynx (10,11) . During oral feeding, the breathing mechanics involves the adequate activation of the diaphragm, intercostal muscles, and the muscles of the upper respiratory tract from the nose until the glottis (10,11) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that swallowing is an activity which is coordinated with other oral functions and require a strict interaction among different muscle groups. For the synchronization of suction and swallowing, it is necessary a strict relationship between the muscles of the oral region to generate suction pressure, to open and close the mouth, and of the tongue to make the bolus and its peristaltic transportation into the pharynx (10,11) . During oral feeding, the breathing mechanics involves the adequate activation of the diaphragm, intercostal muscles, and the muscles of the upper respiratory tract from the nose until the glottis (10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…For the synchronization of suction and swallowing, it is necessary a strict relationship between the muscles of the oral region to generate suction pressure, to open and close the mouth, and of the tongue to make the bolus and its peristaltic transportation into the pharynx (10,11) . During oral feeding, the breathing mechanics involves the adequate activation of the diaphragm, intercostal muscles, and the muscles of the upper respiratory tract from the nose until the glottis (10,11) . Recent studies have noted that hyperplasia of the pharyngeal and palatine tonsils is the second most frequent cause of obstruction of the upper respiratory tract and, consequently, of oral breathing in children (11)(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that the body balance of scholars with mouth breathing, in both genders, are most affected in relation to students without oral breathing, especially in the presence of sensory conflict (25) . In the analysis of sensory systems, there was no statistically significant difference between the mean values obtained for the study and control groups -somatosensory (p=0.64), visual (p=0.37), buccal (p=0.92) and visual preference (p=0.10).…”
Section: Discussionmentioning
confidence: 93%
“…No presente estudo foi possível observar maior número de sujeitos do gênero masculino no grupo respirador bucal, fato que também verificado em outros estudos que compararam sujeitos respiradores bucais e nasais 4,7,9 , mesmo sem hipótese que o justifique na literatura. .…”
Section: Discussionunclassified